Total Aflatoxin Contamination Level in Flour in Mongolia and Aflatoxin Intake - Lkhaasuren, Gerelmaa; Uush, Tserendolgor; Badrakh, Burmaajav; Dorjidagba, Ganzorig; Boldbaatar, Narandelger (Central Asian Journal of Medical Sciences, 2016)
Objectives: This study aimed to assess the total aflatoxin contamination level in flour, flour storage conditions, and the aflatoxin intake in Mongolia. Methods: A total of 71 samples of flour were randomly collected from the survey area in Ulaanbaatar, the capital city of Mongolia, from March to December 2015. An ELISA test was used for detection the total aflatoxins B1 + B2 . The relative humidity and temperatures of the storage areas were measured at the time of sampling the flour. The personal daily intake of aflatoxin was estimated. Results: The survey found that 43.7% of all analyzed flour samples had detectable aflatoxin at 0.04 µg kg-1 and 0.05 µg kg-1. The mean relative humidity and temperatures of the storage areas were higher than the recommended level. The aflatoxin intakes were 0.1271 µg kg-1 body weight day-1 and 0.3615 µg kg-1 body weight day-1 as calculated from the mean daily flour intake and the 95th percentile intake, respectively. Conclusion: The potential health hazard associated with aflatoxin in flour was not determined as a serious threat in Mongolia, but the storage conditions of flour may encourage the growth of fungi-producing aflatoxins. Thus, a national strategy for the elimination of aflatoxin in foods is needed in Mongolia.